Self-Concept In Education Psychology - Yahaya, Azizi (2008)

(untitled)
Self-concept refers to the totality of a complex, organized, and dynamic system of learned beliefs, attitudes and opinions that each person holds to be true about his or her personal existence. Parental upbringing, continuous failure, depression and internal self-critic are factors that influence the development of one’s self-concept. A positive self-concept can be developed through behave objectively in knowing oneself, always appreciate oneself, be friend to oneself and always have a positive and rational thinking. Educational psychology can be referred to a distinct scientific discipline within psychology that includes both method of study and a resulting knowledge base. It is believed that the development of student’s self-concept depends on the focus of educators in educational psychology in classroom practice. Educational psychology provides important background knowledge that pre-service and in-service educators can use as the foundation for professional practice. A positive self-concept can contribute to good academic achievement by student’s optimistic personal expectations about himself or herself.